The West Wing : the American presidency as television drama - Rollins, Peter C.; O'Connor, John E. (Syracuse, N.Y. : Syracuse University Press, 2003)
This work shows that while the series 'The West Wing' may be criticized as 'idealistic', its clever techniques of camera work, lighting, editing and mise en scene reflect America's best image of itself and entertain a loyal audience that wants to believe in the nobility of the American Dream.
The West Wing : White House narratives that journalism cannot tell / Donnalyn Pompper -- The White House culture of gender and race in The West Wing : insights from the margins / Christina Lane -- The West Wing (NBC) and the West Wing (D.C.) : myth and reality in television's portrayal of the White House / Myron A. Levine -- The king's two bodies : identity and office in Sorkin's West Wing / Heather Richardson Hayton -- Dialogue, deliberation, and discourse : the far-reaching politics of The West Wing / Samuel A. Chambers -- The West Wing's textual president : American constitutional stability and the new public intellectual in the age of information / Patrick Finn -- The left takes back the flag : the steadicam, the snippet, and the song in The West Wing's "In excelsis Deo" / Greg M. Smith -- From The American president to The West Wing : a scriptwriter's perspective / Jason P. Vest -- The sincere Sorkin White House, or, the importance of seeming earnest / Pamela Ezell -- The West Wing as a pedagogical tool : using drama to examine American politics and media perceptions of our political system / Staci Beavers -- Victorian parliamentary novels, The West Wing, and professionalism / Michelle Mouton -- Inside The West Wing's new world / Sharon Waxman -- The feel-good presidency : the pseudo-politics of The West Wing / Chris Lehmann -- The liberal imagination / Jon Podhoretz -- The transformed presidency : people and power in the real West Wing / Myron A. Levine.
Includes bibliographical references (pages 261-276) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: West Wing (Television program); West Wing (Television program); The West Wing; West Wing (Television program); POLITICAL SCIENCE -- American Government -- General; Präsident; Fernsehsendung; Inszenierung; Washington <DC> -- Weißes Haus <Motiv>; USA; Aufsatzsammlung; Aufsatzsammlung